Significance of Textural Parameters for Characterization of Clastic Sedimentary Processes: Case Study of Benin Formation, Niger Delta, Nigeria - Okon, E. E.; Essien, N. U.; Ilori, A. O.; Njoku, S. N. (Modern Advances in Geography, Environment and Earth Sciences Vol. 4, 2021)
120 sediment samples collected along a 47 km transect from Ikot Abasi to Eket, southern Nigeria were subjected to granulometric analysis to determine their textural characteristics and depositional processes. Standard sedimentological methods involving sieve analysis were utilized to determine the various size distributions for each sample. Sediment size distribution is a reflection of the fluidity factor of the depositing medium and the energy factor of the environment of deposition. This was further subjected to statistical treatment (mean grain size, median, sorting, kurtosis, skewness, bivariate and multivariate analyses). Results show that the samples are very fine grain to pebbly (3.23 to -1.53) ? diameter in size and varies from very poorly sorted to very well sorted (2.069 to 0.294) ? with about 86% of the samples being poorly sorted. The sediments are predominantly leptokurtic (91%), with only few (9 samples) being platykurtic (range 8.148 to -1.082) ? and are coarse to very fine skewed in nature. The dominant modes of transportation reflected by these sediments are saltation and surface creep attributed mostly to current and channel action. Bivariate analysis revealed that most of the sediments are associated with fluvial processes of deposition with beach processes being subordinate. Multivariate analysis showed that shallow marine agitated environment mostly characterized the sediments of this study area. CM pattern for the sediments reveal deposition was mainly by graded suspension to bottom suspension and rolling. These features characterize sediments deposited by fluvio-deltaic processes dominated by tractive current patterns in a shallow marine depositional environment. The sediments along the studied transect show energy setting associated with a mix of high and relaxed energy at different times during depositional process, reflected in their moderate sorting, predominantly positively skewed and leptokurtic nature.